Defect Reduction Through Customer-Vendor Collaboration In Kaizen - Khor, Li Sing (Universiti Sains Malaysia, 2017)
Lean manufacturing (LM) aims to eliminate operational waste and to maximize product value from customer perspective. This paper investigates ten-weeks customer-vendor joint Kaizen improvement activity to reduce rub mark, a common cosmetic defect on plastic packaging. Whilst noncritical, the entailing inspection and sorting are non-value added. There are assorted of contributing factors, including processing and handling by both vendor and customer. The handling of work requires certain level of sensitivity. Several countermeasures have been implemented and material handling and defect determination at both sides have been standardized. Results gathered showed significant decrease of the defects. Rašković et al. (2012)’s customer-vendor relationship model was used to enhance the understanding of critical elements influencing the success of the case study. Keywords: industry project, internship, lean manufacturing, kaizen, supply chain and vendor improvement.